Barriers to adherence to antiretroviral treatment in a regional hospital in Vredenburg, Western Cape, South Africa - Ivo N. Azia; Ferdinand C. Mukumbang; Brian van Wyk (AOSIS, 2016)
Background: South Africa currently runs the largest public antiretroviral treatment (ART) programme in the world, with over 80% of people living with HIV and/or AIDS on ART. However, in order to appreciate the benefits of using ART, patients are subject to uncompromising and long-term commitments of taking at least 95% of their treatment as prescribed. Evidence shows that this level of adherence is seldom achieved because of a multilevel and sometimes interwoven myriad of factors. Objective: We described the challenges faced by patients on ART in Vredenburg with regard to ART adherence. Methods: A descriptive qualitative research design was used. Eighteen non-adhering patients on ART in the Vredenburg regional hospital were purposefully selected. Using a semistructured interview guide, we conducted in-depth interviews with the study participants in their mother tongue (Afrikaans). The interviews were audio-taped, transcribed verbatim and translated into English. The data were analysed manually using the thematic content analysis method. Results: Stigma, disclosure, unemployment, lack of transport, insufficient feeding, disability grants and alternative forms of therapy were identified as major barriers to adherence, whereas inadequate follow-ups and lack of patient confidentiality came under major criticisms from the patients. Conclusion: Interventions to address poverty, stigma, discrimination and disclosure should be integrated with group-based ART adherence models in Vredenburg while further quantitative investigations should be carried out to quantify the extent to which these factors impede adherence in the community.